Familial Experiences of Caring for Schizophrenia Patients during the Covid-19 Pandemic: A Qualitative Study - Indriati Indriati; Wien Soelistyo Adi; Tuti Anggarawati; Yuni Astuti; Delisa Alfriani (Universitas Airlangga, 2021)
Introduction: Due to the Covid-19 pandemic, families are facing problems caring for and implementing Covid-19 health protocols when caring for schizophrenia patients. A lack of knowledge and behavior changes make it difficult for the families to care for the schizophrenia patients. This study aims to explore the familial experiences of caring schizophrenia patients during the Covid-19 pandemic.Methods: A phenomenological qualitative design was undertaken as of November 2020. A total of 10 participants via the purposive sampling technique were recruited. The study was conducted in Semarang, Indonesia. We used semi-structured interviews to obtain the data and we used thematic content analysis to examine it.Results: From the 10 participants, we got 3 themes, namely family fears, financial problems, and health treatment access. The themes were obtained from the families of the patients who care for them on a daily basis. During the Covid-19 pandemic, caring for schizophrenia patients has become more difficult and the cause of a lot of worry.Conclusion: The families experienced several problems when caring for schizophrenia patients. The families experienced fear of the schizophrenia patients being infected by Covid-19, the families worried about whether or not the schizophrenia patients would experience a relapse and they felt stressed due to the news circulating. The families also had to spend more money to cover the cost of the patient’s care and transportation, and the schizophrenia patients were rarely controlled because of the family’s fears. This problem can be an issue for nurses who should strive to provide proper education and plan interventions for schizophrenia patients at the family level.